A firm’s perspective on econophysics-based currency risk analysis - Fiedor, Paweł; Hołda, Artur (Perspektywa firmy w ekonofizycznej analizie ryzyka walutowego, 2014)
In this article the authors presents an approach to quantifying currency risk based on the methodology of econophysics. This article continues the authors’ study into the currency risk, this time simplifying it for the purpose of rendering it useful for companies without technical abilities. A method of analysing the dependencies between currencies based on correlations is introduced to facilitate the analysis of currency risk involved in being exposed to one or more foreign currencies. Also a model estimating a risk-free horizon is introduced and tested against price formation models and empirical data from FX markets
Nauki o Finansach = Financial Sciences, 2014, Nr 4 (21), s. 92-107
Keywords: risk; exchange rate; predictability; econophysics; ryzyko; kursy walutowe; przewidywalność; ekonofizyka